Design and analysis of experiments - Montgomery, Douglas C. (Hoboken, NJ : John Wiley & Sons, Inc., 2013)
"The eighth edition of Design and Analysis of Experiments continues to provide extensive and in-depth information on engineering, business, and statistics-as well as informative ways to help readers design and analyze experiments for improving the quality, efficiency and performance of working systems. Furthermore, the text maintains its comprehensive coverage by including: new examples, exercises, and problems (including in the areas of biochemistry and biotechnology); new topics and problems in the area of response surface; new topics in nested and split-plot design; and the residual maximum likelihood method is now emphasized throughout the book"--
Machine generated contents note: Chapter 1: Introduction Chapter 2: Simple Comparative Experiments Chapter 3: Experiments with a Single Factor: The Analysis of Variance Chapter 4: Randomized Blocks, Latin Squares, and Related Designs Chapter 5: Introduction to Factorial Designs Chapter 6: The 2k Factorial Design Chapter 7: Blocking and Confounding in the 2k Factorial Design Chapter 8: Two-Level Fractional Factorial Designs Chapter 9: Additional Design and Analysis for Factorial and Fractional Factorial Designs Chapter 10: Fitting Regression Models Chapter 11: Response Surface Methods and Designs Chapter 12: Robust Parameter Design and Process Robustness Studies Chapter 13: Experiments with Random Factors Chapter 14: Nested and Split-Plot Designs Chapter 15: Other Design and Analysis Topics Appendix .
Includes bibliographical references (pages 719-724) and index.
Keywords: Experimental design; TECHNOLOGY & ENGINEERING / Industrial Engineering